Kontribusi Wanita PUI Jawa Barat dalam Bidang Pendidikan, Sosial dan Keagamaan (1995-2016) - Rosmiati, Ai Leni (Historia Madania: Jurnal Ilmu Sejarah, 2020)
This article aims to describe one of the Indonesian Islamic women’s organizations namely Wanita Persatuan Ummat Islam (PUI) or PUI Women. The focus of this study is the contribution of Wanita PUI West Java in the fields of education, social, and religious 1995-2016. The method used in this research is the ristorical research method which is passed through four stages namely heuristics, criticism, interpretation, and historiography. The discussion og this article is the contribution of Wanita PUI or PUI Women in these three fields; education, social, and religious. Also the advantages and disadvantages of this organization. Keyword: Contribution, West Java PUI Women